2007
DOI: 10.4028/www.scientific.net/kem.280-283.651
|View full text |Cite
|
Sign up to set email alerts
|

Converting Industrial TiO<sub>2</sub> into Titanate Nanotubes by Simple Sonochemical-Hydrothermal Processing

Abstract: Slim titanate naotubes was prepared from industrial coarse TiO2 powder by simple sonochemical-hydrothermal processing. The influences of ultrasonic irradiation on TiO2 precursors were investigated. The morphology and crystal structure of the products were characterized by TEM and X-ray diffraction, respectively. The typical products are long nanotubes around 8-10nm in out diameter. Both anatase and rutile TiO2 precursors can be transferred into titanate nanotubes in this sonochemical & hydrothermal process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Cavitational collapse produces intense local heating (∼5000 K), high pressures (∼1000 atm), and enormous heating and cooling rates (>10 9 K/s). The sonochemical method has been applied to prepare various TiO 2 nanomaterials by different groups. Yu et al applied the sonochemical method in preparing highly photoactive TiO 2 nanoparticle photocatalysts with anatase and brookite phases using the hydrolysis of titanium tetraisoproproxide in pure water or in a 1:1 EtOH−H 2 O solution under ultrasonic radiation . Huang et al found that anatase and rutile TiO 2 nanoparticles as well as their mixtures could be selectively synthesized with various precursors using ultrasound irradiation, depending on the reaction temperature and the precursor used .…”
Section: 10 Sonochemical Methodsmentioning
confidence: 99%
“…Cavitational collapse produces intense local heating (∼5000 K), high pressures (∼1000 atm), and enormous heating and cooling rates (>10 9 K/s). The sonochemical method has been applied to prepare various TiO 2 nanomaterials by different groups. Yu et al applied the sonochemical method in preparing highly photoactive TiO 2 nanoparticle photocatalysts with anatase and brookite phases using the hydrolysis of titanium tetraisoproproxide in pure water or in a 1:1 EtOH−H 2 O solution under ultrasonic radiation . Huang et al found that anatase and rutile TiO 2 nanoparticles as well as their mixtures could be selectively synthesized with various precursors using ultrasound irradiation, depending on the reaction temperature and the precursor used .…”
Section: 10 Sonochemical Methodsmentioning
confidence: 99%
“…Sound waves have been also used to synthesize several TiO 2 nanomaterials by a number of groups. [27][28][29][30] Yu et al 31 under ultrasonic irradiation, prepared highly photoactive TiO 2 nanoparticles with anatase and brookite phases using the hydrolysis of titanium tetraisoproproxide in pure water or in a 1:1 (v/v) = Etanol:Water solution. Huang et al 27 found that anatase and rutile titania nanoparticles as well as their mixtures, depending on the reaction temperature and the precursor applied, can be selectively synthesized by sonication.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…Ultrasound irradiation causes rapid formation, growth and collapse of unstable bubbles in liquids, where temperature can be as high as 5000 K and pressures up to 20 MPa and high cooling rates of 10 10 Ks −1 [87]. Several researchers have reported synthesis of titania through this route [88][89][90][91]. Researchers have found that it is possible to synthesize titania phase selectively through manipulation of titania precursors, temperature strength of ultrasound [92,93].…”
Section: Sonochemical Synthesismentioning
confidence: 99%